Une revue des analyses de l’impact économique des plantes transgéniques dans les agricultures non industrialisées - Smale, Mélinda; Niane, Aimée; Zambrano, Patricia (Société Française d'Economie Rurale, 2010)
Based on a systematic search of peer-reviewed, data-based literature published from 1997 to 2007, this article reviews methods used to assess the economic impacts of transgenic crops on farmers in non-industrialized agriculture. A number of methodological limitations are identified, and some improvements recommended. Given methodological constraints, the few case studies conducted in developing economies, and the brief time period of adoption, initial research findings, though generally positive, should be considered with caution.